Convergence criteria for participation in the flexible mechanisms of the Kyoto Protocol - Axel Michaelowa; Michael Dutschke; Marcus Stronzik (Hamburg Institute of International Economics (HWWA), 1999)
The authors suggest a multi-layered system of three convergence criteria – similar to those used in the run-up to the European monetary union – that define the notion of ,,demonstrable progress“ towards reaching the emission commitments under the Kyoto Protocol. These are the existence of an independently evaluated national emissions inventory, the level of domestic policies and measures, and the quantitative convergence of emissions towards the Kyoto target. While the first of these criteria constitutes a necessary condition for participation in the use of flexible instruments, the other two determine the degree of participation allowed for any given Annex I country. – – Wir schlagen - analog zur Bestimmung der Teilnehmer an der Wirtschafts- und Währungsunion in der EU - ein mehrschichtiges System von Konvergenzkriterien vor, die zur Definition des 2005 zu überprüfenden ,,nachweisbaren Fortschritts“ beim Erreichen der Treibhausgasemissionsziele des Kyoto-Protokolls dienen. Die Existenz unabhängig begutachteter Treibhausgasinventare ist unseres Erachtens eine notwendige Bedingung zur Teilnahme an den flexiblen Instrumenten. Das Niveau heimischer Politikmaßnahmen und die quantitative Konvergenz der inländischen Emissionen auf das Kyoto-Ziel hin sollen bestimmen, in welchem Maße die flexiblen Instrumente genutzt werden können.
Keywords: 330; Klimaschutz; Umweltabkommen; Konvergenzkriterien; Welt